Economics : principles, problems, and policies - McConnell, Campbell R. (McGraw-Hill, 2002)
A comprehensive overview of economics that covers national income, employment, fiscal policy, money, banking, monetary policy, macroeconomic debates, microeconomics, international economics, the world economy, supply and demand, and other related topics